Racism: A Part of History That Has Never Been Lost - Farras Kartika Kusumadewi; Moses Glorino Rumambo Pandin (UIN Sunan Gunung Djati Bandung, 2021)
There have been many cases of racism in its history that have occurred from ancient times to the present. Many factors cause racial conflicts. Factors that often trigger these actions, among others, are due to injustice, oppression, and racial discrimination by certain groups against other groups. In America itself, the era of slavery was a dark period in American history. This article aims to find out the impact and solutions to the problem of racism in general. How to find out the impact and solution to the problem of racism is to examine some of the cases that have occurred recently. The method used in this research is qualitative-descriptive with a literature review method to analyze data with 20 sources from books, journal articles, theses and websites. The findings of this study reveal that cases of racism still occur today, for example, last year because of the COVID-19 problem that initially occurred in Wuhan, China, Asian people received hatred from citizens and Western media. There are many factors that cause racial conflict, and the triggers vary in each country that experiences it, among others, because of injustice, oppression, and racial discrimination by certain groups against other groups. Through cases of racism that have occurred, one thing that according to the researcher can be concluded is how before the conflict between groups occurred, actually it started from problems that occurred between individuals. Tolerance is the main thing to stem this kind of thing.